Role of chemokines in regulating luteal and uterine functions in pregnant cows - Ryosuke SAKUMOTO (The Journal of Reproduction and Development, 2024)
Pregnancy is intricately regulated by the interactions between various bioactive substances secreted by the conceptus, uterus, and corpus luteum (CL). Interferon-τ, synthesized and secreted by the conceptus, plays a central role in the interaction mechanism of maternal recognition in cows. Chemokines, chemotaxis mediators that are primarily secreted by immune cells, regulate various reproductive responses in various species. Although there are scattered reports on the potential roles of chemokines in the bovine CL and the uterus during the estrous cycle, there is little information on chemokines in these organs during pregnancy. Therefore, in this review, we discuss the possible physiological roles of chemokines in the CL and uterus of pregnant cows, focusing on our recent findings on chemokines and changes in their receptor expression in the CL and endometrium of cows at some stages of pregnancy.